A Retroperitoneal Inflammatory Pseudotumor involving Duodenum: A Case Report and Review of literature - Sarker, MM; Ali, MS; Sarker, MK; Perveen, NA (TAJ: Journal of Teachers Association, 2018)
Inflammatory pseudotumor or (IPT) is a rare lesion of unclear etiology reported in various organs. Although mostly benign, these tumor may pose a therapeutic challenge in cases of recurrence. We report the case of a 65- years -old male who presented with a mass in the left upper abdomen and upon evaluation was noted to have IPT in the retro-peritoneum involving the duodenum. Complete surgical resection was done with primary repair of the 3rd part of the duodenum with no evidence of tumor recurrence on 6 months follow-up. We review the literature and discern the epidemiological, clinical, pathophysiological and management aspects of IPTs. TAJ 2015; 28(2): 61-63